2021
DOI: 10.1097/ico.0000000000002822
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Cell Loss After Endocapsular and Supracapsular Phacoemulsification: The PERCEPOLIS Randomized Clinical Trial

Abstract: Purpose: Subluxation techniques are superior to divide-andconquer in procedure duration, pain, and ultrasound quantity, but their safety in endothelial cell loss (ECL) is unclear. This randomized single-blind noninferiority clinical trial aimed to determine whether subluxation supracapsular phacoemulsification techniques are inferior to a reference endocapsular technique (divide-andconquer) regarding postoperative corneal ECL.Methods: Patients (aged18 years or older) with greater than +0.2 logarithm of the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 34 publications
1
10
2
Order By: Relevance
“…We read with interest the article entitled “Corneal Endothelial Cell Loss After Endocapsular and Supracapsular Phacoemulsification: The PERCEPOLIS Randomized Clinical Trial.“ 1 The findings of this well-designed study support the noninferiority of a subluxation technique compared with standard in-the-bag phacoemulsification.…”
supporting
confidence: 53%
“…We read with interest the article entitled “Corneal Endothelial Cell Loss After Endocapsular and Supracapsular Phacoemulsification: The PERCEPOLIS Randomized Clinical Trial.“ 1 The findings of this well-designed study support the noninferiority of a subluxation technique compared with standard in-the-bag phacoemulsification.…”
supporting
confidence: 53%
“…It was approved by the Ethics Committee of the French Society of Ophthalmology (IRB 00008855 Société Française d’Ophtalmologie IRB#1) and adhered to the tenets of the Declaration of Helsinki. All subjects provided written informed consent before randomization [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…DAC is an endocapsular method where the nucleus is fractured into four quadrants in the capsular bag and then removed [ 49 ]. Our RCT showed that subluxation is non-inferior to DAC in terms of ECL at 3 months [ 50 ]. In the present study, we conducted a post-hoc analysis of these trial data to assess the ability of nine demographic, preoperative, and perioperative variables to predict ECL 3 months after phacoemulsification.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary outcome analysis also showed that the effective phaco times were similar but subluxation associated with significantly shorter procedure duration. 4…”
mentioning
confidence: 99%
“…Secondary outcome analysis also showed that the effective phaco times were similar but subluxation associated with significantly shorter procedure duration. 4 Knutsson et al first noted that our analyses did not include the fluid volume used during the procedure, which is known to contribute to ECL. 5 We agree that this is a study limitation and are addressing it with a large prospective study that is currently underway in our department.…”
mentioning
confidence: 99%